AN ANALYSIS ON STUDENTSâ SPEAKING SKILL AT SECOND GRADE SMP 8 RAMBAH HILIR - Harahap, Siti Surinah; Antoni, Rivi; Rasyidah, Ummi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research was to find out students speaking skill. Speaking is one of the some skills among listening, writing, reading.This research used descriptive qualitative research design.where the writer described and analyzed the studentsâ errors in speaking skill. The population of this research was taken from the second grade studentsâ at Smp 8 Rambah Hilir in Rambah Hilir district is about 21 students.Based on the result, the writer concludes that the second grade studentsâ of SMP 8 in Rambah Hilir district year 2014/2015 in speaking were good in speaking skill. The result of the analysis showed that 67% out of 21 students have good speaking ability, 33 % of 21 students had average to good speaking ability. No students were in poor to average and poor level ability. The conclusion is the studentsâ speaking skill is good.